(untitled) (The International Journal for Scientific Research, 2024)
The research aims, through its paragraphs, to the following: 1. Providing practical evidence for issues related to the family that appear disparate to the observer, but are closely related to the family situation in its most precise issues, such as personal data, ending with the exercise of legal rights and actions. 2. The research seeks to explain the impact of unifying the legal system within the family in strengthening the personal advantage of its members and their legal authority to acquire rights and bear obligations, and to explain the result of this unification in preserving, caring for, and cohesive the family.